Teatro, sociedade e comparativismo literário: filigranas do discurso jurídico em A Partilha, de Miguel Falabella - Hagemeyer, Jéssica Nágilla (2021)
Based on the studies of Ubersfeld (2005), Ryngaert (1996), Pallottini (1998) and Pavis (1999) about the way in which the theatrical text is structured, also on the postulates of Bachelard (1996) concerning the poetics of space as well as on the contributions of Antonio Candido (2000) regarding the sociological aspects that circumscribe a literary text, associated with the contributions of Lenza (2012) and Venosa (2014) with respect to the Fundamental Rights and the Law of Succession, this research aims to discuss and analyze the legal aspects found in the play A Partilha, by Miguel Falabella. The nature of the methodology is mainly qualitative and descriptive, and the theoretical framework is based on the tenets of Comparative Literature, specifically on the interaction between the Fundamental Rights, connected to the sphere of the Law of Succession, and Literature. From the standpoint of the theatrical discourse, this study proposes an analysis of inheritance issues and their implications in the family environment during the process of inventory and distribution of properties. Bearing in mind that it is a relevant work of Brazilian dramaturgy, as well as a representation of the family quarrels relationships, A Partilha shows itself to be the ideal stage for the socio-legal reflection present in personal relationships. It is indeed important to highlight that in the section “Por entre letras, palcos e telas: o (re)teatralizar de uma bios”, we will go through a biographical overview of the artist Miguel Falabella, as well as his dramaturgy in order to understand the configuration of his aesthetic project. In “Do panorama histórico ao contexto social: na ribalta, A Partilha”, we address the historical moment in which the play was conceived in order to understand the process of artistic creation of the work and the motivating reasons for its elaboration. The reflections included in the section “As filigranas dos Direitos Fundamentais na peça A Partilha” are based on the elements that make up the dramatic action of the play associated with what governs the Fundamental Rights in the field of the Law of Succession and their implications on the family environment. By means of the analysis of the characters’ dialogues, it is possible to understand how a partitioning process is carried out in Brazil, the particularities of the executor’s choices and what their attributions are in this procedural stage. In addition, we point out the significant changes in the civil legislation, from the conception/staging of the play until the current context concerning the inheritance process, in order to monitor the social dynamics of protection of (new) family compositions inscribed in the diegesis. Finally, we found that the play provided a debate on social-affectivity, which has gained prominence in the present-day Fundamental Rights, because it prioritizes the legal protection of the affective bonds built throughout life.